Polymer, thiophene compound, conductive member, and electronic component

By introducing specific imidyl group structural units into the polymer, the water resistance problem of existing conductive polymers during water contact is solved, and a polymer with high conductivity and excellent water resistance is achieved.

CN119522246APending Publication Date: 2025-02-25TDK CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380050855.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-16
Filing Date
2023-07-27
Publication Date
2025-02-25

Smart Images

  • Figure CN119522246A_ABST
    Figure CN119522246A_ABST
Patent Text Reader

Abstract

Provided is a polymer containing a structural unit selected from the group consisting of structural units represented by formula (1) and formula (2) (wherein X represents a divalent linking group). A represents a halogen atom or an alkyl group having 1-5 carbon atoms and having or not having a substituent group. M is a cation. ) of at least one structural unit. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polymer, a thiophene compound, a conductive member and an electronic component.

[0002] The present invention claims priority based on Japanese Patent Application No. 2022-121673 filed on July 29, 2022, and Japanese Patent Application No. 2023-022716 filed on February 16, 2023, the contents of which are incorporated herein by reference. Background Art

[0003] Conductive polymers have electrical conductivity and organic properties different from metals (lightweight, flexibility, humidity sensing, etc.). Therefore, conductive polymers are being studied for use in electronic components used in a wide range of fields such as sensors, capacitors, actuators, lithium-ion secondary batteries, and biological electrodes.

[0004] Conductive polymers are compounds with a π-electron conjugated structure. Generally speaking, conductive polymer monomers lack conductivity. Therefore, a compound (dopant) with high electron accepting or electron donating properties is doped into the conductive polymer to show conductivity. When a dopant as an acceptor is doped into the conductive polymer, π electrons are released from the π-electron conjugated structure to generate holes and holes, thereby showing conductivity. In addition, when a dopant as a donor is doped into the conductive polymer, electrons are supplied from the donor to the π-electron conjugated structure to generate negatively charged negative carriers, thereby showing conductivity.

[0005] In recent years, as a conductive polymer, self-doping conductive polymers that can obtain conductivity without adding dopants from the outside have attracted much attention. Self-doping conductive polymers are compounds in which a group having a dopant function is bonded to a chain structure having a π-electron conjugated structure. Self-doping conductive polymers do not require doping of dopants from the outside, and dopant migration does not occur. Therefore, self-doping conductive polymers have better stability than conductive polymers doped with dopants.

[0006] Examples of self-doping conductive polymers include those described in Patent Documents 1 and 2.

[0007] Patent document 1 describes a thiophene compound, a polythiophene obtained by polymerizing the same, and an aqueous solution of the polythiophene, wherein the thiophene compound has a -SO3M (M represents: a hydrogen atom; an alkali metal selected from Li, Na and K; NH (R 1 )3; or HNC5H5. 1Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may be substituted.

[0008] Patent Document 2 describes, as a structural unit of polythiophene, a unit in which a substituent is bonded to a carbon atom in the ethylenedioxy group of a structural unit containing 3,4-ethylenedioxythiophene. As a substituent, a terminal having -C(R)SO3M (R represents a chain or branched alkyl group having 1 to 6 carbon atoms, or a fluorine atom. M represents: a hydrogen atom; an alkali metal selected from Li, Na and K; NH(R 1 )3; or HNC5H5. 1 Each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms which may be substituted. - (R represents a linear or branched alkyl group having 1 to 6 carbon atoms, or a fluorine atom.) Patent Document 2 also describes an aqueous solution of polythiophene.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent No. 6040615

[0012] Patent Document 2: Japanese Patent No. 6131780 Summary of the invention

[0013] [Technical problem to be solved by the invention]

[0014] However, the existing self-doping conductive polymer is water-soluble. Therefore, the existing conductive member containing the self-doping conductive polymer dissolves the self-doping conductive polymer when in contact with water, and sometimes cannot maintain the shape or the conductivity decreases. Therefore, in the existing conductive member containing the self-doping conductive polymer and the electronic component using the same, it is required to improve the water resistance.

[0015] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a self-doping conductive polymer having low hydrophilicity and good lipophilicity, which can form a conductive member having sufficient conductivity and excellent water resistance.

[0016] Another object of the present invention is to provide a thiophene compound which has sufficient conductivity and can be used as a raw material monomer for a self-doping conductive polymer having low hydrophilicity and good lipophilicity.

[0017] Another object of the present invention is to provide a conductive member having excellent water resistance and comprising the polymer of the present invention, and an electronic component including the conductive member.

[0018] [Technical solutions for solving technical problems]

[0019] In order to solve the above technical problems, the following technical solutions are provided.

[0020] The polymer according to one embodiment of the present invention is a polymer containing at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2).

[0021]

[0022] (In the general formula (1), X represents a divalent linking group. A represents a halogen or an alkyl group having 1 to 5 carbon atoms which may have a substituent.)

[0023] (In the general formula (2), X represents a divalent linking group. A represents a halogen or an alkyl group having 1 to 5 carbon atoms which may have a substituent. M represents a cation.)

[0024] [Effects of the invention]

[0025] The polymer of the present invention contains at least one structural unit selected from the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2). Therefore, the polymer of the present invention is a self-doping conductive polymer with low hydrophilicity and good lipophilicity, and can be suitably used as a material capable of forming a conductive member having sufficient conductivity and excellent water resistance.

[0026] The thiophene compound of the present invention is represented by the general formula (3). Therefore, by polymerizing the raw material monomers containing the thiophene compound of the present invention, the polymer of the present invention, i.e., the self-doping conductive polymer having sufficient conductivity, low hydrophilicity and good lipophilicity, can be produced.

[0027] Furthermore, the conductive member and the electronic component including the conductive member of the present invention contain the polymer of the present invention. Therefore, the conductive member and the electronic component including the conductive member of the present invention have excellent water resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a diagram showing the results of analyzing the polymer of Example 1 by total reflection measurement using a Fourier transform infrared spectrophotometer (FT-IR).

[0029] Figure 2 is the thiophene compound synthesized in Example 1 1 H-NMR measurement chart.

[0030] Figure 3 This is a diagram showing the results of analyzing the polymer of Example 1 using GPC (gel permeation chromatography). DETAILED DESCRIPTION

[0031] In order to solve the above technical problems, the inventors of the present invention have conducted intensive studies focusing on substituents having a dopant function bonded to a carbon atom in an ethylenedioxy group of a structural unit containing 3,4-ethylenedioxythiophene in a self-doping conductive polymer having a structural unit containing 3,4-ethylenedioxythiophene.

[0032] As a result, it was found that any polymer containing a structural unit having a group in which a specific imide group as a substituent having a dopant function is bonded to a carbon atom in the ethylenedioxy group of 3,4-ethylenedioxythiophene via a divalent linking group is sufficient.

[0033] In the polymer, the substituent having a dopant function bonded to the carbon atom of the ethylenedioxy group in the structural unit containing 3,4-ethylenedioxythiophene is a group formed by bonding a specific imide group via a divalent linking group, and therefore the polymer is a self-doping conductive polymer having excellent water resistance. As a result, it is inferred that, for example, a conductive component containing a polymer having a substituent having a dopant function as described above can obtain more excellent water resistance than a conductive component containing a polymer having a sulfonate group such as -SO3Na (the imide group of the substituent having a dopant function is replaced by the group).

[0034] In addition, the inventors of the present invention produced a conductive member containing a polymer containing a structural unit having a group formed by bonding a specific imide group to a carbon atom in the ethylenedioxy group of 3,4-ethylenedioxythiophene via a divalent linking group, and confirmed that the conductive member had good water resistance and sufficient conductivity, thereby completing the present invention.

[0035] The present invention includes the following aspects.

[0036] [1] A polymer comprising at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2).

[0037]

[0038] (In the general formula (1), X represents a divalent linking group. A represents a halogen or an alkyl group having 1 to 5 carbon atoms which may have a substituent.)

[0039] (In the general formula (2), X represents a divalent linking group. A represents a halogen or an alkyl group having 1 to 5 carbon atoms which may have a substituent. M represents a cation.)

[0040] [2] The polymer according to [1], wherein in the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2),

[0041] The above-mentioned X is a divalent linking group represented by the general formula (L-Ar).

[0042] (In the general formula (L-Ar), L represents a single bond or a divalent linking group. Ar represents any one selected from a phenylene group which may have a substituent, a biphenylene group which may have a substituent, and a naphthylene group which may have a substituent.)

[0043] [3] The polymer described in [2], wherein the above L is represented by the following general formula (L-a), the above Ar is a phenylene group, and the above A is a fluorine atom, or an alkyl group having 1 to 5 carbon atoms in which at least a part of the hydrogen atoms are substituted with fluorine atoms.

[0044]

[0045] (In the general formula (L-a), L1, L2, and L3 each independently represent any one selected from a single bond, an alkylene group having 1 to 2 carbon atoms, and an ether bond.)

[0046] [4] The polymer according to [1], wherein in the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2),

[0047] The above X is a chain structure in which a plurality of alkylene groups are connected via ether bonds.

[0048] [5] A thiophene compound, wherein the thiophene compound is represented by the following general formula (3).

[0049]

[0050] (In the general formula (3), X represents a divalent linking group. A represents a halogen or an alkyl group having 1 to 5 carbon atoms which may have a substituent. M represents a cation.)

[0051] [6] The thiophene compound according to [5], wherein in the general formula (3), X is a divalent linking group represented by the general formula (L-Ar).

[0052] (In the general formula (L-Ar), L represents a single bond or a divalent linking group. Ar represents any one selected from a phenylene group which may have a substituent, a biphenylene group which may have a substituent, and a naphthylene group which may have a substituent.)

[0053] [7] The thiophene compound described in [6], wherein the above L is represented by the following general formula (L-a), the above Ar is a phenylene group, and the above A is a fluorine atom, or an alkyl group having 1 to 5 carbon atoms in which at least a part of the hydrogen atoms are substituted with fluorine atoms.

[0054]

[0055] (In the general formula (L-a), L1, L2, and L3 each independently represent any one selected from a single bond, an alkylene group having 1 to 2 carbon atoms, and an ether bond.)

[0056] [8] The thiophene compound according to [5], wherein in the general formula (3), X is a chain structure in which a plurality of alkylene groups are connected via ether bonds.

[0057] [9] A conductive member comprising the polymer according to any one of [1] to [4].

[0058]

[10] An electronic component comprising the conductive member described in [9].

[0059] Hereinafter, the polymer, thiophene compound, conductive member and electronic component of the present invention will be described in detail.

[0060] [polymer]

[0061] The polymer (self-doped conductive polymer) of this embodiment contains at least one structural unit selected from the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2). In the solid state of the polymer of this embodiment, the state of the structural unit represented by the general formula (1) and the state of the structural unit represented by the general formula (2) are in equilibrium. The ratio of the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) in the polymer of this embodiment is not particularly limited.

[0062] The structural unit represented by the general formula (1) shows the doping state of the structural unit represented by the general formula (2). In the polymer of this embodiment, the substituent having a dopant function (-X-SO2-N - M-SO2A) contained in the imide salt (-SO2-N -M-SO2A) is a dopant. The cation (M) in the structural unit represented by the general formula (2) contained in the polymer of this embodiment may exist in the polymer in a cationic state or in a state bonded to a nitrogen atom in the imide salt.

[0063] The imide salt contained in the structural unit represented by the general formula (2) is doped into the structural unit represented by the general formula (1), thereby taking away π electrons from the π electron conjugated structure of the thiophene ring forming the polymer main chain, and generating positive charges (holes). That is, the polymer of this embodiment is a self-doping conductive polymer that can obtain conductivity without adding a dopant from the outside.

[0064] In the polymer of this embodiment, the substituent having a dopant function (-X-SO2-N - -SO2A) and the substituent having a dopant function in the structural unit represented by the general formula (2) (-X-SO2-N - M-SO2A) can be bonded to any one of the two carbon atoms of the ethylenedioxy group of 3,4-ethylenedioxythiophene. In addition, in the multiple structural units forming the polymer of this embodiment, the bonding positions of the substituent having a dopant function relative to the carbon atom of the ethylenedioxy group can be all the same or partially different.

[0065] In the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) possessed by the polymer of the present embodiment, X represents a divalent linking group. X is preferably a chain structure containing one or more selected from any one of an arylene group, an alkylene group, and an ether bond in any order. In order to form a self-doped conductive polymer with lower hydrophilicity and better lipophilicity, X preferably contains an arylene group. In the case where X contains an arylene group, it is more preferred that the arylene group contained in X is bonded to the sulfur atom of the imide salt.

[0066] In the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), X is preferably a divalent linking group represented by the general formula (L-Ar). In the general formula (L-Ar), L represents a single bond or a divalent linking group, and Ar represents any one selected from a phenylene group with or without a substituent, a biphenylene group with or without a substituent, and a naphthylene group with or without a substituent. In the general formula (L-Ar), the valence bond on the left is bonded to the carbon atom of the ethylenedioxy group of the structural unit containing 3,4-ethylenedioxythiophene, and the valence bond on the right is bonded to the sulfur atom of the imide salt in the polymer of this embodiment.

[0067] In the case where L in the divalent linking group represented by the general formula (L-Ar) is a divalent linking group, a self-doped conductive polymer with better water resistance will be formed compared to the case where L is a single bond, and thus it is preferred. In the case where L is a divalent linking group, it is preferably a divalent linking group with a chain structure formed by one or more alkylene groups and one or more ether bonds, and more preferably the number of carbon atoms in the divalent linking group is 1 to 8. In the case where L is a divalent linking group, when the number of carbon atoms in the divalent linking group is 8 or less, the chain structure of the divalent linking group will not be too long, the molecular chain arrangement of the polymer of this embodiment will not become difficult, and the conductivity of the polymer will not become insufficient, and thus it is preferred. As a divalent linking group with a carbon number of 8 or less, for example, -(CH2) can be listed. 1~8 O-, -O(CH2) 1~8 -, -O(CH2) 1~8 O-, -O(CH2)2O(CH2)2-, -CHO2O(CH2)2OCH2-, -CH2O(CH2)2O-, -CH2OCH2-, etc.

[0068] L in the divalent linking group represented by the general formula (L-Ar) is preferably a divalent linking group represented by the general formula (L-a). In the general formula (L-a), L1 is bonded to the carbon atom of the ethylenedioxy group of the structural unit containing 3,4-ethylenedioxythiophene, and L3 is bonded to Ar. In the general formula (L-a), L1, L2, and L3 are each independently selected from a single bond, an alkylene group having 1 to 2 carbon atoms, and an ether bond. Specifically, -CH2OCH2- (L1 = alkylene group having 1 carbon atom, L2 = ether bond, L3 = alkylene group having 1 carbon atom), -CH2O- (L1 = alkylene group having 1 carbon atom, L2 = ether bond, L3 = single bond,), -(CH2)2O- (L1 = alkylene group having 2 carbon atoms, L2 = ether bond, L3 = single bond), -O(CH2) 1~2 -(L1 = ether bond, L2 = alkylene group having 1 to 2 carbon atoms, L3 = single bond), -O(CH2) 1~2 O—(L1=ether bond, L2=alkylene group having 1 to 2 carbon atoms, L3=ether bond), etc., preferably —CH 2 OCH 2 — or —CH 2 O—, because it forms a polymer that can be easily produced.

[0069] In the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) possessed by the polymer of the present embodiment, Ar represents any one selected from a phenylene group with or without a substituent, a biphenylene group with or without a substituent, and a naphthylene group with or without a substituent. In order to facilitate production, Ar is preferably an unsubstituted phenylene group.

[0070] Examples of the substituent in the phenylene group which may be substituted, the biphenylene group which may be substituted, and the naphthylene group which may be substituted include a fluorine atom, a methyl group, an ethyl group, a methoxy group, an ethoxy group, an acetyl group, a carbomethoxy group, and a cyano group.

[0071] In the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) possessed by the polymer of the present embodiment, X can be a chain structure formed by connecting multiple alkylene groups via ether bonds. In this case, the total number of carbon atoms and oxygen atoms contained in the chain structure is preferably 3 to 20. When the total number of carbon atoms and oxygen atoms is 20 or less, the chain structure will not be too long, the molecular chain arrangement of the polymer of the present embodiment will not become difficult, and the conductivity of the polymer will not become insufficient, so it is preferred. The total number of carbon atoms and oxygen atoms contained in the chain structure is more preferably 3 to 12. As such a chain structure, specifically, for example, -CH2O(CH2)2OCH2-, -CH2O(CH2)3OCH2-, -CH2O(CH2)3-, -CH2OCH2-, -(CH2)2OCH2-, -CH2O(CH2)2-, -CH2O(CH2)4-, etc. can be cited. Among these, -CH2O(CH2)2-, -CH2O(CH2)3-, and -CH2O(CH2)4- are preferred because they form polymers that can be easily synthesized. In these specific chain structures, the left-side bond is bonded to the carbon atom of the ethylenedioxy group of the structural unit containing 3,4-ethylenedioxythiophene, and the right-side bond is bonded to the sulfur atom of the imide salt in the polymer of this embodiment.

[0072] In the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2) contained in the polymer of the present embodiment, A represents a halogen or an alkyl group having 1 to 5 carbon atoms which may have a substituent.

[0073] Examples of the substituent on the optionally substituted alkyl group having 1 to 5 carbon atoms include halogen groups such as fluoro, chloro, and bromo; alkyl groups such as methyl and ethyl; alkoxy groups such as methoxy and ethoxy; and cyano.

[0074] A in the polymer of this embodiment is preferably a fluorine atom, or an alkyl group having 1 to 5 carbon atoms in which at least a part of the hydrogen atoms are replaced by fluorine atoms, and more preferably an alkyl group having 1 to 3 carbon atoms in which all the hydrogen atoms are replaced by fluorine atoms (perfluoroalkyl group). The reason is that it will become a self-doping conductive polymer with lower hydrophilicity and better lipophilicity, and it will become a polymer that can form a conductive component with better water resistance.

[0075] In the structural unit represented by the general formula (2) in the polymer of the present embodiment, M represents a cation, and examples thereof include -Li + , -Na + , -K + , -H + , pyridinium (-[C5H5HN] + ), ammonium ion (-N + H(R 1 )3(The three R in the formula 1 Each independently represents a hydrogen atom or an alkyl group having 1 to 15 carbon atoms which may be substituted. )) etc. As the cation (M), i.e., ammonium ion, specifically, -N + H3C2H4OH (the above formula -N + H(R 1 )The three Rs in 3 1 Two of them are hydrogen atoms and the remaining one is R 1 is an ethyl group having one hydroxyl group as a substituent. ) etc. In order to form a self-doping conductive polymer with better conductivity, M is preferably selected from -Na + , -H + , -N + Any of H3C2H4OH, particularly preferably -H + .

[0076] In the polymer of the present embodiment, the substituent having a dopant function (-X-SO2-N - M-SO2A) is a divalent linker (X) bonded to an imide salt (-SO2-N - Therefore, even if the cation (M) contained in the substituent having the dopant function is -Na + , -K + Cations that easily form highly hydrophilic polymers can also form self-doping conductive polymers with excellent water resistance.

[0077] The degree of polymerization of the polymer of the present embodiment is not particularly limited, and is preferably in the range of 3 to 5000. When the degree of polymerization of the polymer is 3 or more, a self-doping conductive polymer with more excellent water resistance will be formed. The degree of polymerization of the polymer is more preferably 10 or more. When the degree of polymerization of the polymer is 10 or more, a self-doping conductive polymer with more excellent water resistance and better conductivity will be formed. In addition, when the degree of polymerization of the polymer is 5000 or less, a self-doping conductive polymer with sufficient solubility in the solvent is formed. Therefore, the process adaptability and productivity when manufacturing a conductive component containing the polymer of the present embodiment are excellent.

[0078] [Method for producing polymer]

[0079] [Thiophene compounds]

[0080] When producing the polymer of this embodiment, first, raw material monomers containing a thiophene compound represented by the general formula (3) are prepared.

[0081] X, A and M in the thiophene compound represented by the general formula (3) are the same as X, A and M in the structural unit represented by the general formula (2).

[0082] [Method for producing thiophene compound]

[0083] The thiophene compound represented by the general formula (3) can be manufactured, for example, by the method shown below. First, a halogen compound (D1-X0-SO2-D2, wherein: D1, D2 are halogens; X0 is a part of X in the general formula (2)) having a structure corresponding to a part of a substituent having a dopant function in the structural unit represented by the general formula (2) is prepared by a conventionally known method.

[0084] As the halogen compound, for example, 4-(bromomethyl)benzenesulfonyl chloride, 4-(chloromethyl)benzenesulfonyl chloride, 4-fluorobenzenesulfonyl chloride, 4-(2-bromoethoxy)benzenesulfonyl chloride, 3-chloropropanesulfonyl chloride and the like can be used.

[0085] The above-mentioned halogen compound can be synthesized by a known method, or a commercially available product can be used.

[0086] Next, D2 in the above-mentioned halogen compound and NH2 in the sulfonamide (NH2-SO2-A (A is the same as A in the general formula (2))) having a terminal group corresponding to A in the general formula (2) are reacted in the presence of a compound containing a cationic species that becomes M in the general formula (2) to obtain an intermediate compound.

[0087] As the sulfonamide having a terminal group corresponding to A, for example, trifluoromethanesulfonamide, pentafluoroethanesulfonamide, heptafluoropropanesulfonamide, 1,1,2,2,3,3,4,4,4-nonafluorobutanesulfonamide, methanesulfonamide, ethanesulfonamide, etc. can be used.

[0088] The above-mentioned sulfonamide having a terminal group corresponding to A can be synthesized by a known method, or a commercially available product can be used.

[0089] In the general formula (2), M is Na + In the case of M, as the compound containing a cationic species to become M, for example, anhydrous sodium carbonate, sodium hydroxide, etc. can be used.

[0090] In the general formula (2), M is K +In the case of M, as the compound containing a cationic species to be M, for example, anhydrous potassium carbonate, potassium hydroxide, etc. can be used.

[0091] Next, the obtained intermediate compound is reacted with a compound in which a group corresponding to a part of X in the general formula (2) is bonded to a carbon atom in the ethylenedioxy group of 3,4-ethylenedioxythiophene. Thus, a substituent having a dopant function (-X-SO2-N - A thiophene compound represented by the general formula (3) in which M-SO2A) is bonded to a carbon atom in the ethylenedioxy group of 3,4-ethylenedioxythiophene.

[0092] As a compound in which a group corresponding to a part of X in the general formula (2) (e.g., a hydroxyl group) is bonded to a carbon atom in the ethylenedioxy group of 3,4-ethylenedioxythiophene, for example, (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol can be used.

[0093] Reaction conditions such as reaction temperature and reaction time when producing the thiophene compound represented by the general formula (3) can be appropriately determined depending on the type of the thiophene compound represented by the general formula (3) and the like.

[0094] In the thiophene compound represented by the general formula (3), the substituent (-X-SO2-N - M-SO2A) contained in the imide salt (-SO2-N - M-SO2A) contains cation (M). Therefore, the thiophene compound represented by the general formula (3) is dissolved in a solvent, and the cation (M) can be easily exchanged for the desired cation by exchanging the type of cation using a cation exchange resin corresponding to the desired cation.

[0095] As the solvent used when exchanging the cation (M) of the thiophene compound represented by the general formula (3), for example, 2-methylpyrrolidone, acetone, dimethylformamide, dimethylacetamide, tetrahydrofuran, acetonitrile or the like can be used.

[0096] Examples of cation exchange resins that can be used when exchanging the cations (M) contained in the thiophene compound represented by the general formula (3) include the following resins.

[0097] For example, when M in the thiophene compound represented by the general formula (3) is changed from -Na + Changed to -H +In the case of using cation exchange resins, LEWATIT MonoPlus S108H (manufactured by Lanxess), ORTLITE DS-01 (manufactured by Organo), AMBERLYST 15JS-HG·DRY (manufactured by Organo), etc. can be used.

[0098] In addition, for example, when M in the thiophene compound represented by the general formula (3) is changed from -H + Changed to -Na + In the case of , as the cation exchange resin, LEWATIT MonoPlus S108 (manufactured by Lanxess) or the like can be used.

[0099] In addition, since the imide salt contained in the thiophene compound represented by the general formula (3) contains a cation (M), for example, when M in the thiophene compound represented by the general formula (3) is -H + And want to make M become -N + H3C2H4OH and other ammonium ions (-N + H(R 1 )3(The three R in the formula 1 Each independently represents a hydrogen atom or an alkyl group having 1 to 15 carbon atoms which may be substituted. In the case of )), by using a compound having the same structure as the above-mentioned formula -N such as ethanolamine + H(R 1 )3 in R 1 The thiophene compound represented by the general formula (3) can be easily changed by using an amine compound of a corresponding group as a neutralizing agent for neutralization.

[0100] For example, in the thiophene compound represented by the general formula (3), M is -Na + When it is desired to convert M into an ammonium ion, the above-mentioned method using a cation exchange resin is used to convert -Na + Changed to -H + Then, M of the thiophene compound represented by the general formula (3) can be easily changed by neutralizing it with an amine compound corresponding to the desired ammonium ion.

[0101] [Method for producing polymer]

[0102] For example, the polymer of this embodiment can be produced by chemically oxidatively polymerizing raw material monomers containing the thiophene compound represented by the general formula (3) using a polymerization initiator such as sodium persulfate or potassium persulfate and an oxidant such as ferric chloride by a known method.

[0103] The polymerization conditions such as the reaction temperature, reaction time, and the amount of the polymerization initiator used when producing the polymer of the present embodiment can be appropriately determined according to the composition of the raw material monomers and the like.

[0104] The raw material monomers used in the method for producing the polymer of the present embodiment may contain only one thiophene compound represented by the general formula (3), or may contain two or more thiophene compounds represented by the general formula (3) as required. In addition, the raw material monomers may contain not only the thiophene compound represented by the general formula (3), but may contain one or more known monomers in addition to the thiophene compound represented by the general formula (3) as required.

[0105] Examples of known monomers that may be contained in the raw material monomers include 3,4-ethylenedioxythiophene, 2-(chloromethyl)-2,3-dihydrothieno[3,4-b]-1,4-dioxin, and (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol.

[0106] The type and content of the known monomers can be appropriately determined in accordance with the intended use of the polymer, etc., within a range in which the effects of the present invention can be obtained.

[0107] The polymer of this embodiment has a substituent having a dopant function (-X-SO2-N - Therefore, in the polymer of the present embodiment, the imide salt (—SO2—N - M-SO2A) contains a cation as M in the general formula (2).

[0108] Therefore, the polymer of the present embodiment can easily exchange the cation (M) for a desired cation, similarly to the thiophene compound represented by the general formula (3).

[0109] Specifically, the polymer of the present embodiment can be easily exchanged with a desired cation by dissolving the polymer in a solvent and exchanging the type of cation using a cation exchange resin corresponding to the desired cation.

[0110] Examples of the solvent that can be used to dissolve the polymer of the present embodiment include 2-methylpyrrolidone, acetone, dimethylformamide, dimethylacetamide, tetrahydrofuran, and acetonitrile.

[0111] For example, in the polymer of the present embodiment, M is -H + And want to make M become -N +In the case of H3C2H4OH, the polymer of the present embodiment can be easily changed by a method of neutralizing using ethanolamine as a neutralizing agent.

[0112] [Conductive member]

[0113] The conductive member of the present embodiment contains the polymer of the present embodiment. Hereinafter, a sheet-shaped conductive member is cited as an example of the conductive member of the present embodiment for explanation. The conductive member of the present embodiment can be in any shape as long as it contains the polymer of the present embodiment, and is not limited to the sheet shape.

[0114] The polymer of the present embodiment contained in the conductive member of the present embodiment may be only one kind or may be two or more kinds. In addition, as required, the conductive member of the present embodiment may contain one or two or more well-known polymers other than the polymer of the present embodiment together with the polymer of the present embodiment. In addition, as required, the conductive member of the present embodiment may also contain one or two or more well-known conductive materials together with the polymer of the present embodiment.

[0115] As known polymers that can be contained in the conductive component of the present embodiment, for example, known conductive polymers such as a composite of poly (3,4-ethylenedioxythiophene) and polystyrene sulfonic acid (PEDOT / PSS), acrylic resins such as polymethyl methacrylate, vinyl acetal resins such as polyvinyl butyral, phenol novolac, thermosetting resins such as epoxy resins, silicone resins such as polydimethylsiloxane, fluororesins such as polyvinylidene fluoride, polystyrene, styrene butadiene rubber, polyacrylonitrile, polyethylene glycols, ethyl cellulose, cellulose nanofibers, etc. can be listed.

[0116] Examples of known conductive materials that may be contained in the conductive member of the present embodiment include metal materials such as copper, gold, nickel, and aluminum; and carbon materials such as graphite, activated carbon, graphene, and carbon nanotubes.

[0117] The conductive member of the present embodiment can be produced by, for example, the method described below.

[0118] The conductive material containing the polymer of the present embodiment, which will become the conductive member of the present embodiment, is dissolved in a known solvent such as dimethylformamide, acetone, dimethylacetamide, tetrahydrofuran, acetonitrile, etc. to form a coating liquid. Then, the coating liquid is applied to a substrate that can be peeled off with a specified thickness to form a coating film. As a substrate, a known substrate composed of a resin film such as polyethylene terephthalate (PET) can be used. The coating method of the coating liquid can use a known method according to the coating thickness, the viscosity of the coating liquid, etc. Afterwards, the coating film is dried, the solvent in the coating film is removed, and it is peeled off from the substrate to obtain a sheet-like conductive member.

[0119] [Electronic components]

[0120] The electronic component of this embodiment includes the conductive member of this embodiment.

[0121] Specific examples of the electronic component of the present embodiment include sensors, capacitors, actuators, lithium ion secondary batteries, and biological electrodes.

[0122] The electronic component of the present embodiment can be produced by providing a conductive member containing the polymer of the present embodiment by a known method.

[0123] The polymer of this embodiment contains at least one structural unit selected from the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2). Therefore, the polymer of this embodiment is a self-doping conductive polymer with low hydrophilicity and good lipophilicity, has sufficient conductivity, and can be applied to a material capable of forming a conductive component with excellent water resistance. In addition, since the polymer of this embodiment is a self-doping conductive polymer, it does not require an external dopant and does not cause migration of the dopant, so it has excellent stability.

[0124] The thiophene compound of this embodiment is represented by general formula (3). Therefore, by polymerizing the raw material monomer containing the thiophene compound of this embodiment, a self-doping conductive polymer having sufficient conductivity, low hydrophilicity and good lipophilicity, that is, the polymer of this embodiment, can be produced.

[0125] In addition, in the polymer and the thiophene compound of the present embodiment, the substituent (—X—SO 2 —N - M-SO2A) contained in the imide salt (-SO2-N - M-SO2A) contains cations (M). Therefore, for the polymer and thiophene compound of this embodiment, the cation (M) can be easily changed to a desired cation by using the following methods: dissolving the polymer and thiophene compound of this embodiment in a solvent and exchanging the cation type using a cation exchange resin corresponding to the desired cation; or neutralizing the polymer and thiophene compound of this embodiment using a neutralizer.

[0126] In addition, the conductive member of the present embodiment and the electronic component including the conductive member contain the polymer of the present embodiment. Therefore, the conductive member of the present embodiment and the electronic component including the conductive member have excellent water resistance.

[0127] Although the embodiments of the present invention have been described in detail above, each structure of each embodiment and their combination are merely examples, and addition, omission, substitution, and other changes in structure may be made without departing from the gist of the present invention.

[0128] Example

[0129] [Example 1]

[0130] [Method for producing thiophene compound]

[0131] (Synthesis of Intermediate Compound (a-1))

[0132] In a two-necked eggplant flask equipped with a reflux tube, 5.53 g of trifluoromethanesulfonamide (37.1 mmol, manufactured by Tokyo Chemical Industry Co., Ltd.), 2.36 g of anhydrous sodium carbonate (22.2 mmol, manufactured by Kishida Chemical Co., Ltd.) and 20 mL of dehydrated acetonitrile (manufactured by Kanto Chemical Co., Ltd.) were added under a nitrogen stream, and the flask was cooled in ice water. Then, a mixed solution of 5.00 g of 4-(bromomethyl)benzenesulfonyl chloride represented by formula (a-0) (18.6 mmol, manufactured by Tokyo Chemical Industry Co., Ltd.) and 20 mL of dehydrated acetonitrile was added dropwise to the flask, and heated at 70° C. for 12 hours while stirring.

[0133] After cooling, 100 mL of ethyl acetate was added, and the inorganic salts were removed by filtration. The filtrate was concentrated by a rotary evaporator to obtain a crude product. The crude product was dissolved in acetone and purified by reprecipitation using cyclopentyl methyl ether. Thus, a white solid consisting of the intermediate compound represented by formula (a-1) was obtained (yield 5.32 g).

[0134]

[0135] (Synthesis of Thiophene Compound (a-2))

[0136] In a two-necked eggplant flask equipped with a reflux tube, 0.46 g (10.5 mmol, manufactured by Kanto Chemical Co., Ltd.) of 55% sodium hydride, 1.72 g (9.98 mmol, manufactured by Kanto Chemical Co., Ltd.) of (2,3-dihydrothieno[3,4-b][1,4]dioxin-2-yl)methanol and 20 mL of dehydrated tetrahydrofuran (manufactured by Kanto Chemical Co., Ltd.) were added under a nitrogen stream, and refluxed for 1 hour.

[0137] After cooling, a mixed solution of 3.63 g (8.99 mmol) of the intermediate compound (a-1) synthesized by the above reaction and 10 mL of dehydrated tetrahydrofuran was added dropwise to the flask, and the mixture was heated under reflux for 16 hours.

[0138] After cooling, 200 mL of ethyl acetate was added, and the inorganic salts were removed by filtration. The filtrate was concentrated by a rotary evaporator to obtain a crude product. The product was dissolved in acetone and purified by reprecipitation using cyclopentyl methyl ether and silica gel column chromatography. Thus, a white solid composed of the thiophene compound represented by formula (a-2) was obtained (yield 2.85 g).

[0139] The obtained thiophene compound is subjected to 1 H-NMR (nuclear magnetic resonance) determination. 1 In the H-NMR measurement, JNM-ECA500 (manufactured by JEOL RESONANCE) was used as the NMR apparatus. 1 In the H-NMR measurement, deuterated solvent dimethyl sulfoxide d6 (DMSO-d6) was used as the solvent. The results are as follows Figure 2 and as shown below. Figure 2 is the thiophene compound synthesized in Example 1 1 H-NMR measurement chart.

[0140] The obtained thiophene compound was subjected to mass analysis using an Agilent 6100 Quadrupole MS (manufactured by Agilent Technologies) as a mass spectrometer and an electrospray ionization (ESI) method.

[0141] According to the following 1 As a result of H-NMR measurement and mass analysis, it was confirmed that the synthesized thiophene compound was the thiophene compound represented by formula (a-2).

[0142] 1 H-NMR (500MHz, deuterated DMSO) δ (ppm) 7.71-7.68 (2H, m), 7.40-7.39 (2H, m), 6.57-6.54 (2H, m), 4.57(2H,s), 4.36-4.33(1H,m), 4.26-4.23(1H,m), 4.02-3.98(1H,m), 3.66-3.65(2H,m)

[0143] m / z 471([M-]C 15 H 13 F3NO7S)

[0144] (Synthesis of polymer (P-1))

[0145] Add 97.7 mg (0.197 mmol) of the raw material monomer, thiophene compound represented by formula (a-2), to a glass bottle and dissolve it in 900 mg of pure water. Then, add 19.2 mg of FeCl3 (0.118 mmol, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), 93.9 mg of sodium persulfate (0.395 mmol, manufactured by Junsei Chemical Co., Ltd.) and a mixed aqueous solution of 900 mg of pure water, cover the glass bottle, and vigorously stir at room temperature for 3 hours to perform chemical oxidative polymerization. Thus, a dark blue solid is generated.

[0146] After that, 2 mL of pure water was added to the glass bottle, and the dark blue solid was recovered by filtration. The dark blue solid was washed with pure water to remove impurities such as inorganic salts. The washed dark blue solid was added to acetone for ultrasonic treatment, and the inorganic salts were filtered out using a filter with a pore size of 0.22 μm.

[0147] The filtrate was concentrated using a rotary evaporator to obtain the target polymer represented by formula (P-1).

[0148]

[0149] The polymer of Example 1 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) (Nicoleti S10, manufactured by Thermo Fisher Scientific) to determine its molecular structure.

[0150] Figure 1 1 is a graph showing the results of analyzing the polymer of Example 1 using a Fourier transform infrared spectrophotometer (FT-IR) by total reflection measurement. Figure 1 As shown, at wave numbers 4000 to 1800 cm -1 Characteristic spectral band absorption caused by doping was observed in the range of .

[0151] As a result, it was confirmed that the polymer of Example 1 was a polymer represented by formula (P-1) containing a structural unit represented by formula (P11) and a structural unit represented by formula (P21).

[0152] In addition, the number average molecular weight (Mn), weight average molecular weight (Mw), and degree of dispersion (Mw / Mn) of the polymer of Example 1 were determined by the following methods.

[0153] First, the polymer of Example 1 was dissolved in the following mobile phase to a concentration of 0.5 W / V%, and filtered using a filter composed of polytetrafluoroethylene (PTFE) with a mesh size of 0.45 μm to prepare a sample solution. The obtained sample solution was analyzed using GPC (gel permeation chromatography) (LC-2050C; manufactured by Shimadzu Corporation) under the following measurement conditions. The results are shown in Figure 3 middle.

[0154] (Measurement conditions)

[0155] Injection volume: 20 μL

[0156] Column: TSKgelα-M (manufactured by TOSOH) 2 pieces + guard column α

[0157] Column temperature: 50°C

[0158] Mobile phase: DMSO (dimethyl sulfoxide) solution containing 50 mM tetrabutylammonium bromide

[0159] Flow rate: 0.3ml / min

[0160] Detector: UV detector 620nm (photodiode array detector)

[0161] Standard substance: Pullulan (manufactured by Showa Denko K.K.)

[0162] Figure 3 This is a graph showing the results of analyzing the polymer of Example 1 using GPC (gel permeation chromatography) and the relationship between the weight average molecular weight (Mw) of pullulan as a standard substance and the retention time (minutes).

[0163] The number average molecular weight (Mn) calculated from the results of GPC analysis of the polymer of Example 1 was 33,300, the weight average molecular weight (Mw) was 74,500, and the degree of dispersion (Mw / Mn) was 2.23.

[0164] [Example 2]

[0165] The polymer represented by the formula (P-1) produced in the same manner as in Example 1 was dissolved in 2-methylpyrrolidone, and the type of cation was changed from -Na to -Na using a cation exchange resin consisting of LEWATIT MonoPlus S108H (manufactured by Lanxess). + Exchange to -H + , thereby obtaining the target polymer represented by formula (P-2).

[0166]

[0167] As with the polymer of Example 1, the polymer of Example 2 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) to determine its molecular structure.

[0168] As a result, it was confirmed that the polymer of Example 2 was a polymer represented by formula (P-2) containing the structural unit represented by formula (P12) and the structural unit represented by formula (P22).

[0169] [Example 3]

[0170] The polymer represented by the formula (P-2) produced in the same manner as in Example 2 was neutralized with ethanolamine to change the type of cation from -H + Change to -N + H3C2H4OH, thereby obtaining the target polymer represented by formula (P-3).

[0171]

[0172] As with the polymer of Example 1, the polymer of Example 3 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) to determine its molecular structure.

[0173] As a result, it was confirmed that the polymer of Example 3 was a polymer represented by formula (P-3) containing the structural unit represented by formula (P13) and the structural unit represented by formula (P23).

[0174] [Example 4]

[0175] The target polymer represented by formula (P-4) was obtained in the same manner as in Example 1 except that pentafluoroethanesulfonamide (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of trifluoromethanesulfonamide when synthesizing the intermediate compound (a-1).

[0176]

[0177] As with the polymer of Example 1, the polymer of Example 4 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) to determine its molecular structure.

[0178] As a result, it was confirmed that the polymer of Example 4 was a polymer represented by formula (P-4) containing the structural unit represented by formula (P14) and the structural unit represented by formula (P24).

[0179] [Example 5]

[0180] The polymer represented by the formula (P-4) produced in the same manner as in Example 4 was dissolved in 2-methylpyrrolidone, and the type of cation was changed from -Na to -Na using a cation exchange resin consisting of LEWATIT MonoPlus S108H. + Exchange to -H + , thereby obtaining the target polymer represented by formula (P-5).

[0181]

[0182] As with the polymer of Example 1, the polymer of Example 5 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) to determine its molecular structure.

[0183] As a result, it was confirmed that the polymer of Example 5 was a polymer represented by formula (P-5) containing the structural unit represented by formula (P15) and the structural unit represented by formula (P25).

[0184] [Example 6]

[0185] When synthesizing the intermediate compound (a-1), except that 4-fluorobenzenesulfonyl chloride (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of 4-(bromomethyl)benzenesulfonyl chloride represented by formula (a-0), the same operation as that of the polymer represented by formula (P-1) produced in Example 1 was carried out to obtain the target polymer represented by formula (P-6).

[0186]

[0187] As with the polymer of Example 1, the polymer of Example 6 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) and its molecular structure was determined.

[0188] As a result, it was confirmed that the polymer of Example 6 was a polymer represented by formula (P-6) containing the structural unit represented by formula (P16) and the structural unit represented by formula (P26).

[0189] [Example 7]

[0190] The polymer represented by the formula (P-6) produced in the same manner as in Example 6 was dissolved in 2-methylpyrrolidone, and the type of cation was changed from -Na to -Na using a cation exchange resin consisting of LEWATIT MonoPlus S108H.+ Exchange to -H + , thereby obtaining the target polymer represented by formula (P-7).

[0191]

[0192] As with the polymer of Example 1, the polymer of Example 7 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) and its molecular structure was determined.

[0193] As a result, it was confirmed that the polymer of Example 7 was a polymer represented by formula (P-7) containing the structural unit represented by formula (P17) and the structural unit represented by formula (P27).

[0194] [Example 8]

[0195] When synthesizing the intermediate compound (a-1), pentafluoroethanesulfonamide (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of trifluoromethanesulfonamide, and 4-fluorobenzenesulfonyl chloride (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of 4-(bromomethyl)benzenesulfonyl chloride represented by formula (a-0). Except for this, the same operation as the polymer represented by formula (P-1) produced in Example 1 was carried out to obtain the target polymer represented by formula (P-8).

[0196]

[0197] As with the polymer of Example 1, the polymer of Example 8 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) to determine its molecular structure.

[0198] As a result, it was confirmed that the polymer of Example 8 was a polymer represented by formula (P-8) containing the structural unit represented by formula (P18) and the structural unit represented by formula (P28).

[0199] [Example 9]

[0200] The polymer represented by the formula (P-8) produced in the same manner as in Example 8 was dissolved in 2-methylpyrrolidone, and the type of cation was changed from -Na to -Na using a cation exchange resin consisting of LEWATIT MonoPlus S108H. + Exchange to -H + , thereby obtaining the target polymer represented by formula (P-9).

[0201]

[0202] As with the polymer of Example 1, the polymer of Example 9 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) and its molecular structure was determined.

[0203] As a result, it was confirmed that the polymer of Example 9 was a polymer represented by formula (P-9) containing the structural unit represented by formula (P19) and the structural unit represented by formula (P29).

[0204] [Example 10]

[0205] The target polymer represented by formula (P-10) was obtained in the same manner as in Example 1 except that methanesulfonamide (manufactured by Tokyo Chemical Industry Co., Ltd.) was used instead of trifluoromethanesulfonamide when synthesizing the intermediate compound (a-1).

[0206]

[0207] As with the polymer of Example 1, the polymer of Example 10 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) and its molecular structure was determined.

[0208] As a result, it was confirmed that the polymer of Example 10 was a polymer represented by formula (P-10) containing a structural unit represented by formula (P10) and a structural unit represented by formula (P20).

[0209] [Example 11]

[0210] When synthesizing the polymer (P-1), as the raw material monomer, a mixture of the thiophene compound represented by the formula (a-2) and 3,4-ethylenedioxythiophene (wherein, in terms of molar ratio, the thiophene compound represented by the formula (a-2) : 3,4-ethylenedioxythiophene = 95:5) is used instead of the thiophene compound represented by the formula (a-2). Except for this, the same operation as that for the polymer represented by the formula (P-1) produced in Example 1 is performed to obtain the target polymer represented by the formula (P-11).

[0211]

[0212] As with the polymer of Example 1, the polymer of Example 11 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) and its molecular structure was determined.

[0213] As a result, it was confirmed that the polymer of Example 11 was a polymer represented by formula (P-11) containing a structural unit represented by formula (P111), a structural unit represented by formula (P211), a structural unit represented by formula (P3), and a structural unit represented by formula (P4).

[0214] In addition, according to 1 The results of H-NMR measurement confirmed that the ratio of the total of the structural units represented by formula (P111) and formula (P211) in the polymer represented by formula (P-11) to the total of the structural units represented by formula (P3) and formula (P4) was 94:6 in terms of molar ratio (Formula (P111) and formula (P211) : Formula (P3) and formula (P4)).

[0215] [Example 12]

[0216] The target polymer represented by formula (P-12) was obtained in the same manner as in Example 1 except that 3-chloropropanesulfonyl chloride (manufactured by Sigma-Aldrich) was used instead of 4-(bromomethyl)benzenesulfonyl chloride when synthesizing the intermediate compound (a-1).

[0217]

[0218] As with the polymer of Example 1, the polymer of Example 12 was confirmed to be doped with the imide salt as a dopant by total reflectance measurement (ATR) using a Fourier transform infrared spectrophotometer (FT-IR) and its molecular structure was determined.

[0219] As a result, it was confirmed that the polymer of Example 12 was a polymer represented by formula (P-12) containing the structural unit represented by formula (P112) and the structural unit represented by formula (P212).

[0220] [Comparative Example 1]

[0221] Using the method described in Patent Document 1, a polymer represented by the formula (Q-1) containing the structural unit represented by the formula (Q11) and the structural unit represented by the formula (Q21) is obtained.

[0222]

[0223] [Comparative Example 2]

[0224] By using the method described in Patent Document 2, a polymer represented by the formula (Q-2) containing the structural unit represented by the formula (Q12) and the structural unit represented by the formula (Q22) is obtained.

[0225]

[0226] For the polymers (P-1) to (P-12), (Q-1) and (Q-2) of Examples 1 to 12 and Comparative Examples 1 to 2, Table 1 shows L and Ar when they are applied to the general formula (L-Ar) (wherein, for (P-12), this is X when it is applied to the general formula (2)), and M and A when they are applied to the general formula (2), respectively.

[0227] Furthermore, conductive films (conductive members) were formed by the following method using polymers (P-1) to (P-12), (Q-1), and (Q-2) of Examples 1 to 12 and Comparative Examples 1 to 2, respectively, and water resistance was evaluated.

[0228] [Water resistance evaluation]

[0229] The polymer was dissolved in dimethylformamide to prepare a coating liquid. Next, the coating liquid was applied on a PET film and dried at 100° C. to obtain a conductive film (conductive member) having a film thickness of 5 μm.

[0230] The conductivity of the conductive film on the obtained PET film was measured by a four-probe method, and the conductivity was defined as the initial conductivity.

[0231] Thereafter, the PET film on which the conductive film was formed was immersed in pure water for 30 minutes, taken out of the water and air-dried to prepare a water-immersed sample.

[0232] The appearance of the sample after immersion in water was visually observed to evaluate whether the conductive film was peeled off from the PET film. The results are shown in Table 1.

[0233] In addition, the conductivity of the conductive film on the PET film of the sample after immersion in water was measured using the four-terminal method, and this was referred to as the conductivity after immersion in water. Then, using the initial conductivity and the conductivity after immersion in water, the change in conductivity after immersion in water was calculated ((conductivity after immersion in water / initial conductivity)×100(%)), and evaluation was performed based on the criteria shown below. The results are shown in Table 1.

[0234] [Benchmark]

[0235] The change in conductivity is less than ±20%: A.

[0236] The change in conductivity is less than ±50%: B.

[0237] The change in conductivity is more than ±50%: C.

[0238] Unmeasurable (the conductive film peeled off from the PET film due to water immersion): D.

[0239]

[0240] As shown in Table 1, the conductive films containing polymers (P-1) to (P-12) of Examples 1 to 12 all have sufficient initial conductivity, the change in conductivity after immersion in water is evaluated as A or B, and the conductive films in the samples after immersion in water do not peel off from the PET film.

[0241] In addition, the conductive film containing a polymer (P-1) wherein A is a perfluoroalkyl group (CF3) has a conductivity change after immersion in water evaluated as A, and has better water resistance than the conductive film containing a polymer (P-10) wherein A is an alkyl group (CH3) without a substituent.

[0242] In addition, the conductive film containing a polymer (P-1) in which Ar is a phenylene group is evaluated as A in terms of the change in conductivity after immersion in water, and has better water resistance than a conductive film containing a polymer (P-12) in which X is a chain structure (CH2OCH2CH2CH2) formed by two alkylene groups connected by an ether bond when applied to the general formula (2) (in other words, -CH2CH2- is present in the polymer (P-1) instead of a phenylene group).

[0243] On the other hand, the conductive film containing the polymer (Q-1) of Comparative Example 1 had insufficient initial conductivity, and the conductive film in the sample after immersion in water peeled off from the PET film, indicating insufficient water resistance.

[0244] In addition, the conductive film containing the polymer (Q-2) of Comparative Example 2 had a high initial conductivity, but the conductive film in the sample after immersion in water was peeled off from the PET film, indicating insufficient water resistance.

Claims

1. A polymer, wherein Contains at least one structural unit selected from the group consisting of a structural unit represented by the following general formula (1) and a structural unit represented by the following general formula (2), In the general formula (1), X represents a divalent linking group, A represents a halogen, or an alkyl group having 1 to 5 carbon atoms which may have a substituent, In the general formula (2), X represents a divalent linking group, A represents a halogen or an alkyl group having 1 to 5 carbon atoms which may have a substituent, and M represents a cation.

2. The polymer according to claim 1, wherein In the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), The X is a divalent linking group represented by the general formula (L-Ar), In the general formula (L-Ar), L represents a single bond or a divalent linking group, and Ar represents any one selected from an optionally substituted phenylene group, an optionally substituted biphenylene group, and an optionally substituted naphthylene group.

3. The polymer according to claim 2, wherein The L is represented by the following general formula (L-a), the Ar is a phenylene group, the A is a fluorine atom, or an alkyl group having 1 to 5 carbon atoms in which at least a part of the hydrogen atoms are substituted with fluorine atoms, In the general formula (L-a), L1, L2, and L3 each independently represent any one selected from a single bond, an alkylene group having 1 to 2 carbon atoms, and an ether bond.

4. The polymer according to claim 1, wherein In the structural unit represented by the general formula (1) and the structural unit represented by the general formula (2), The X is a chain structure formed by connecting multiple alkylene groups via ether bonds.

5. A thiophene compound, wherein The thiophene compound is represented by the following general formula (3): In the general formula (3), X represents a divalent linking group, A represents a halogen or an alkyl group having 1 to 5 carbon atoms which may have a substituent, and M represents a cation.

6. The thiophene compound according to claim 5, wherein In the general formula (3), X is a divalent linking group represented by the general formula (L-Ar), In the general formula (L-Ar), L represents a single bond or a divalent linking group, and Ar represents any one selected from an optionally substituted phenylene group, an optionally substituted biphenylene group, and an optionally substituted naphthylene group.

7. The thiophene compound according to claim 6, wherein The L is represented by the following general formula (L-a), the Ar is a phenylene group, the A is a fluorine atom, or an alkyl group having 1 to 5 carbon atoms in which at least a part of the hydrogen atoms are substituted with fluorine atoms, In the general formula (L-a), L1, L2, and L3 each independently represent any one selected from a single bond, an alkylene group having 1 to 2 carbon atoms, and an ether bond.

8. The thiophene compound according to claim 5, wherein In general formula (3), The X is a chain structure formed by connecting multiple alkylene groups via ether bonds.

9. A conductive member, in, Contains the polymer according to any one of claims 1 to 4.

10. An electronic component, wherein: The conductive member according to claim 9 is included.

Citation Information

Patent Citations

  • Indirect extruding device of metallic billet

    JP1985040615A

  • Valve device for fluid

    JP1986031780A

  • Biointroducing cosolvent and method of using same

    JP2022121673A

  • Antivibration mount and antivibration structure

    JP2023022716A